Peningkatan Motivasi Belajar Siswa Dengan Menggunakan Media Audiovisual Dalam Pembelajaran Seni Budaya Dan Keterampilan Kelas IX-I Di SMP Negeri 1 Bilah Hulu Kabupaten Labuhan Batu - Theresia Situmorang; Aprinaldi simarangkir; Diana M. Situmeang; Roy J.M Hutagalung; Robert K.A Simangunsong (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to determine the use of increasing student learning motivation by using audiovisual media in learning arts and culture and skills at SMP Negeri 1 Bilah Hulu, Labuhan Batu Regency. The data collection technique used was carrying out a pretest and posttest and observation using the classroom action research method. The results of the research showed that in cycle I, student learning motivation was at a percentage of 46.6% with a medium category range, then after improvements were made, student motivation increased in cycle II with a percentage of 100% with a very high category range. Followed by the results of teacher observations in cycle I with a percentage of 70.7% in the good category, then in cycle II it increased to 89.5% in the very good category. Then the results of student observations in cycle I were 57%, then in cycle II it increased to 89.2 in the very good category. Based on the research results and data analysis above, it can be concluded that the application of the use of audiovisual media can increase the learning motivation of class IX1 students in SBDK subjects. Increasing student learning motivation by using audiovisual media can be declared successful.